BRMP-03. Pituitary carcinoma: a case of dramatic response to immunotherapy (ipilimumab + nivolumab) after failure with temozolomide. (12th November 2021) - Shah, Sanjit; Manzoor, Saima; Rothman, Yehudit; Hagen, Matthew; Prater, Luke; Golnik, Karl; Mahammedi, Abdelkader; Lin, Andrew; Bhabhra, Ruchi; Forbes, Jonathan; Sengupta, Soma
Abstract: INTRODUCTION: Pituitary carcinoma (PC) accounts for just 0.1% of all pituitary tumors, often recurs following resection, and has a median reported survival of 1 year. Current treatment guidelines are not standardized but combine surgical resection, radiation therapy, and chemotherapy [1]. Temozolomide is the only chemotherapeutic with documented effectiveness, and the only recommended agent for aggressive pituitary carcinomas in ESE clinical guidelines [3]. CASE: A 57-year-old male presented with visual deterioration over a three-month period. Ophthalmologic evaluation revealed bitemporal visual field deficits. MRI brain W/WO demonstrated a sellar mass suspected to be pituitary macroadenoma with displacement of the stalk and optic nerve impingement (Figure 1a). The patient underwent stereotactic endoscopic transsphenoidal resection of the mass [2]. Postoperative MRI demonstrated gross total resection (Figure 1b). Pathology revealed a sparsely granulated corticotroph-adenoma with malignant transformation (early in-situ PC). Immunohistochemistry showed LOE of MLH1 and PMS2 in the tumor cells; Genetic analysis revealed MGMT methylation. Proton therapy was recommended given the elevated Ki67 index (75%) and p53 positivity. Before radiotherapy, there was no evidence of residual tumor or metastasis radiographically. He received 6600cGy of radiation over 33 fractions. Surveillance MRI showed recurrence at 21 months postoperatively, and temozolomide was initiated. However, MRI demonstrated marked progression after 3 cycles, and at 44 months, he developed a new 6 th nerve palsy (Figure1c). Next-generation sequencing using the MSK-IMPACT platform identified somatic mutations in MLH1 Y548lfs*9 and TP53 R337C[4]. Immunotherapy with ipilimumab/nivolumab was initiated [5], and the patient noted resolution of his third nerve palsy soon after. MRI demonstrated a dramatic response with only minimal residual tumor burden (Figure1d). CONCLUSION: PC is a rare tumor with frequent recurrence and a short median expected length of survival. Here we demonstrate the utility of immunotherapy in a single case report of PC. This treatment helped our patient survive well beyond the expected median life expectancy of this aggressive disease.